2019
DOI: 10.1002/ceat.201800468
|View full text |Cite
|
Sign up to set email alerts
|

Direct Contact Membrane Distillation Applied to Colored Reactive or Disperse Dye Solutions

Abstract: The influence of dye class and chromogen groups of dyeing wastewaters composed by reactive or disperse dyes with different colors on direct contact membrane distillation (DCMD) was investigated. The state-of-the-art shows that disperse dyes and different dye colors are not studied in DCMD and the application of DCMD for dyeing wastewater treatment is limited to a few publications. High color rejection was obtained and water was recovered at the permeate side for feed solutions containing reactive or disperse d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(2 citation statements)
references
References 31 publications
(36 reference statements)
0
2
0
Order By: Relevance
“…In another work conducted by the same group, the surface hydrophobicity of the neat PP membrane fabricated by the TIPS method was 98°. Wang et al and Ramlow and co-works , reported the WCA for the commercial PP membranes as 118° and used them in the MD process.…”
Section: Results and Discussionmentioning
confidence: 99%
“…In another work conducted by the same group, the surface hydrophobicity of the neat PP membrane fabricated by the TIPS method was 98°. Wang et al and Ramlow and co-works , reported the WCA for the commercial PP membranes as 118° and used them in the MD process.…”
Section: Results and Discussionmentioning
confidence: 99%
“…10 Hydrophobic polymers including polytetrauoroethylene (PTFE), polyvinylidene uoride (PVDF), polyethylene (PE) and polypropylene (PP) have been investigated as a membrane material in the DCMD process. 11,12 Of these, PVDF is favorable, as it has a high solubility for commonly used polar aprotic solvents such as N-methyl-2-pyrrolidone (NMP), 13 N,N-dimethylformamide (DMF) 14 and N,N-dimethylacetamide (DMAC). 15 It has been extensively used for preparing membranes by coating, 16 electrospinning, 5 phase inversion method, 17 thermally induced phase separation (TIPS) 18 and a few more.…”
Section: Introductionmentioning
confidence: 99%